Diferenças individuais no comportamento forrageiro de Polistes versicolor Olivier, 1872 (Vespidae, Polistinae) - Brocanelli, Felipe Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Polistes versicolor is one of the most studied and known species of its genus in Brazil. It occurs throughout the national territory, is well adapted to human environment, lacks morphological caste differences and thus its hierarchical system is mainly based on behavioral features, distinguished by dominance/subordination acts. For feeding their larvae mainly with animal protein (most of them Lepidoptera caterpillars), Polistes wasps show great potential in biological control programs, possibly preying on some pests that attack economically important crops to men. This way, this study aimed to assess some biological features and processes related to hierarchy formation on P. versicolor colonies as well, in order to see their relationship with foraging activities. This work's outcomes show what many other studies have seen; queens found their nests either alone or in groups, and nest foundations are asynchronic, which can occur from August to April. One winter aggregation was observed during the cold season (May - August). Data collection on hierarchy formation and foraging behavior in some nests ensured us to say that the dominant wasp is one of the most aggressive individuals, and also spends most of its time at the comb, without leaving it. Relative age of these queens varied between nests; in some cases they were the oldest, in some the youngest and in some they presented intermediate ages. The trips executed by foragers allowed us to affirm that each resource shows a trend to be collected in specific periods along the day, depending on the colony needs. In average, water trips lasted less than other materials, while returns with animal protein lasted longer. It was not found any kind of relation between the position on ranking of wasps and the type of resource explored by each one. Some prey samples were genetically identified, most of them belonging to order Lepidoptera (7 families). Moreover, other four orders were recognized, ...

Polistes versicolor é uma das espécies mais estudadas e conhecidas do gênero no Brasil. Ocorre em todo o território nacional, é bem adaptada ao ambiente antropizado, não possui diferenciação morfológica de castas e por isso seu sistema de hierarquia é baseado principalmente em aspectos comportamentais, distinguidos por atos de dominância e subordinação. Por alimentar suas larvas principalmente com proteína animal (maioria oriunda de lagartas de lepidópteros), as vespas do gênero, inclusive da presente espécie apresentam um grande potencial promissor como controladores biológicos, muitas vezes de pragas de cultivos agrícolas economicamente importantes para o homem. Dessa forma, o presente trabalho visou acompanhar características da biologia e dos processos associados à construção da hierarquia dos indivíduos da colônia com a finalidade de relacioná-las com seu comportamento forrageiro e as principais espécies de presas utilizadas na sua alimentação. Os resultados encontrados corroboram observações de estudos já realizados de que ninhos de P. versicolor exibem ambas estratégias de fundação - haplo e pleometrose -, bem como a assincronia dessas fundações, que ocorreram ao longo de grande período do ano (agosto - abril). Foi constatada também a presença dos chamados agregados de inverno ao longo da estação fria (maio - agosto). Observações pontuais realizadas acerca da formação da hierarquia e do comportamento forrageiro em alguns ninhos possibilitaram inferir que a vespa dominante é um dos indivíduos que mais exibem comportamentos agressivos contra outros, bem como é o que passa quase todo o tempo no ninho, sem realizar atividades de campo. A idade relativa das poedeiras variou entre ninhos, ora sendo uma das mais velhas, ora a mais nova, ou em níveis intermediários. A análise das viagens executadas pelas forrageiras permitiu associar que os diferentes recursos tendem a ser explorados em...
Keywords: Wasps; Vespa; Animais - Alimentos; Codigo genético; Sociedades de insetos